التعلم الذاتي المنظم في كتابة البحث العلمي باللغة العربية لدى طلبة الدراسات العليا = Autonomous learning in research writing in Arabic language among postgraduate students - Daud, Nadwah; Md Azmi, Nur Afiqah (المجلة الأكاديمية للبحوث والدراسات, 2020)
إن التعلم الذاتي المنظم في عملية التعلم من مواصفات المنعلم الناجح حيث يهيء التعلم المستمر لأن المتعلم المنظم ذاتيا لم يكن معتمدا على المعلم في التعلم. ومن المفترض أن يتصف طلبةالدراسات العليا بالتعلم الذاتي المنظم حيث إنه عليه بإجراء دراسات ثم كتابة تقارير لها ونظرا إلى كونهم في المرحلة الدراسية المتقدمة. ولكن، توجد دراسات تدل على عدم اتصاف طلبة الدراسات العليا به مما يؤدي ذلك إلى تساؤلات في اتصاف طلبة الدراسات العليا به في هذه الجامعة وخاصة في كتابة البحوث العلمية باللغة العربية. إذن تهدف هذه المقالة إلى معرفة مستوى التعلم الذاتي المنظم لدى طلبة الدراسات العليا في كتابة البحوث العلمية. ووُزِّعت استبانة تبنّت من عدة مقاييس تقيس أربعة مكونات، وهي: تحديد الأهداف والمراقبة والتقويم وإبقاء التشجيع، إلى 125 طالبا وطالبة الدراسات العليا من قسم اللغة العربية وآدابها. وأشارت النتيجة إلى أن الطلبة مارسوا التعلم الذاتي المنظم بشكل مرتفع كما هو المتوقع. ********************************************************************************** In learning process, autonomous learning is considered as one of the characteristics of the successful learner, in which it provides continuous learning when the learners becoming less dependent on teacher during learning. Seeing that postgraduate students are advanced in the level of study, they are supposedly practicing autonomous learning as they are required to carry out research and writing report. However, a research showed that postgraduate students are not considered as autonomous learners. It leads to an inquiry whether postgraduate students in this university are practicing autonomous learning or not, especially in writing research in Arabic Thus, this research aims to identify the level of autonomous learning among postgraduate students when writing research in Arabic. The questionnaire was distributed among 125 respondents from Department of Arabic Language and Literature. This questionnaire was constructed from several scales which measure four main components of autonomous learning; identifying objectives, monitoring, selfevaluation and self- motivation. As expected, the result shows the higher level of practicing autonomous learning among students.